'Exploring stuttering severity in the Egyptian Arabic speaking children who stutter: A correlation study of Bloodstein classification of stuttering severity and the stuttering severity instrument for children and Adults-Arabic Version'. (October 2019) - Khodeir, Mona Sameeh
Abstract: Objective: The aim of this study was to explore the magnitude of stuttering severity in the Egyptian Arabic speaking children who stutter (CWS) by corelating stuttering severity grades assessed by Bloodstein classification of stuttering severity (BLS) and by the stuttering severity instrument for children and adults-Arabic version (ASSI). Methods: 58 Egyptian Arabic speaking CWS aged 5–9 years and 9 months, were selected conveniently upon inclusion and exclusion criteria from patients frequented at the Phoniatrics clinic of El-Demerdash hospital (Ain Shams University). Through an observational cross-sectional study, the selected children underwent the Ain Shams university assessment protocol of fluency disorders, including clinician's assessment of stuttering severity by BLS classification and ASSI. The correlation between the grade of stuttering severity by BLS classification and ASSI were analyzed by Spearman's correlation coefficient and regression analysis. Results: Significant positive correlation was found between grades of stuttering severity measured by BLS classification and ASSI. Among children with mild, moderate and severe degrees of stuttering by BLS classification, the score of their ASSI decrease as the child's age increases. The age of the participated CWS was significantly inversely related to the score of ASSI, yet it is not related to the grades of BLS classification. The age of onset of stuttering was not related to stuttering severity whether measured by BLS classification or ASSI. Conclusion: There is a significant positive relationship between stuttering severity measured by BLS classification and ASSI. Speech disfluencies counted by ASSI decreases as the child's age increases, in relation to stuttering severity by BLS classification. Clinicians should depend on more than one tool while assessing stuttering severity.